Evaluation of biochemical properties of peach and nectarine cultivars and Hybrids - Pandey, Swapnil; Thakur, Anirudh; Singh, Harminder (The Indian Journal of Agricultural Sciences, 2020)
Prunes are now occupying an important position in subtropical climates with respect to fruit crop diversification and human health. In the present study, 4 hybrids and 6 cultivars of sub tropical peaches and nectarines were evaluated for their phenolic content and antioxidant activity during 2015-16 and 2016-17. Total phenolic content (mg/100 g) and antioxidant capacity (%) present in the pulp was evaluated at Department of Fruit Science, PAU, Ludhiana (Punjab) India. During the study, it was found that the phenol content ranged between 10.32-51.21 mg/100 g in the year 2015-16 and 10.50-51.67 mg/100 g mg in 2016-17 among the hybrids and cultivars. The antioxidant capacity ranged between 63.51-83.25% in the year 2015-16 and 65.00-84.64% in 2016-17 among the hybrids and cultivars selected for study. Overall, peach and nectarines are rich in phenolic compounds and antioxidant activities and can serve as excellent sources of phyto-chemicals and natural antioxidants. Further, it can be concluded that a large variability exists for these compounds, which offers the scope for selection of superior cultivars and the hybrids.